Assessment of the content, structure, and source of soil dissolved organic matter in the coastal wetlands of Jiaozhou Bay, China. (February 2018) - Xi, Min; Zi, Yuanyuan; Wang, Qinggai; Wang, Sen; Cui, Guolu; Kong, Fanlong
Abstract: The contents and the spectral analysis of dissolved organic matter (DOM) in four typical wetlands, such as naked tidal, suaeda salsa, reed and spartina, were conducted to investigate the content, structure, and source of DOM in coastal wetland soil. The soil samples were obtained from Jiaozhou Bay in January, April, July, and October of 2014. Results showed that the DOM contents in soil of four typical wetland were in order of spartina wetland > naked tidal > suaeda salsa wetland > reed wetland in horizontal direction, and decreased with the increase of soil depth on vertical section. In addition, the DOM contents changed with the seasons, in order of spring > summer > autumn > winter. The structural characteristics of DOM in Jiaozhou Bay wetland, such as aromaticity, hydrophobicity, molecular weight, polymerization degree of benzene ring carbon frame structure and so on were in order of spartina wetland > naked tidal > suaeda salsa wetland > reed wetland in the horizontal direction. On the vertical direction, they showed a decreasing trend with the increase of soil depth. The results of three dimensional fluorescence spectra and fluorescence spectrum parameters (FI, HIX, and BIX) indicated that the DOM in Jiaozhou Bay was mainly derived from the biological activities. The contents and structure of DOM had certain relevance, but the contents and source as well as the structure and source of DOM had no significant correlation. The external pollution including domestic sewage, industrial wastewater, and aquaculture sewage affected the correlation among the content, structure and source of DOM by influencing the percentage of non-fluorescent substance in DOM and disturbing the determination of protein-like fluorescence. Highlights: We investigated the source of DOM in coastal wetland soil. The spatial change of DOM content and structure in coastal wetland soil was analyzed. The temporal change of DOM content and structure in coastal wetland soil was explored. The relationships among content, structure and source of DOM was revealed.